2022
DOI: 10.1002/app.52404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclophosphazene nucleated hyperbranched polyester on flame retardancy and mechanical properties of epoxy resins

Abstract: Hexakis(4-hydroxyphenoxy) cyclotriphosphazene (PN-OH) was synthesized by a nucleophilic substitution and aldehyde reduction reaction of hexachlorocyclotriphosphazene with p-hydroxybenzaldehyde, and then cyclophosphazene nucleated hyperbranched polyesters (HBP) were prepared via a one-pot esterification reaction of PN-OH and dimethylolpropionic acid. The chemical structure and molecular weight distribution of HBP were confirmed by 1 H-NMR, FTIR, and GPC. The HBP was applied to epoxy resin (EP) to improve its me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…DMP, as a cocuring agent, endowed the modified EP composite with better fire safety performance and well-preserved mechanical properties than pure EP. In addition, Figure d and Table S6 exhibited the THR and TSP decline ratios of EP/8DMP and previous EP with P-containing HBPs (EP/P-containing HBPs). ,,,, It could be found that EP/8DMP showed the highest THR and TSP decline ratios of 51.9 and 53.4%, respectively. Therefore, the as-designed EP/8DMP possessed the best fire safety performance among all EP/P-containing HBP composites listed in Table S6.…”
Section: Resultsmentioning
confidence: 91%
“…DMP, as a cocuring agent, endowed the modified EP composite with better fire safety performance and well-preserved mechanical properties than pure EP. In addition, Figure d and Table S6 exhibited the THR and TSP decline ratios of EP/8DMP and previous EP with P-containing HBPs (EP/P-containing HBPs). ,,,, It could be found that EP/8DMP showed the highest THR and TSP decline ratios of 51.9 and 53.4%, respectively. Therefore, the as-designed EP/8DMP possessed the best fire safety performance among all EP/P-containing HBP composites listed in Table S6.…”
Section: Resultsmentioning
confidence: 91%